Effect of Crack Length on Fracture Behavior of Particleboard - Yan Wang; Arif Caglar Konukcu (BioResources, 2022)
The effect of crack length on the fracture behavior of particleboard was investigated using the single-edge-notched bending (SENB) test method under mode I loading. The initial slope (kinit), critical stress intensity factor (KIC), specific fracture energy (Gf), and brittleness number were calculated for five different crack length/specimen width (a/W) ratios varying from 0.1 to 0.9 at intervals of 0.2. The results show that the fracture properties were significantly higher for specimens with an a/W ratio of 0.1 than for the others. However, for the critical stress intensity factor and specific fracture energy, there were no significant differences among the a/W ratios of 0.3, 0.5, and 0.7 where the crack tip was placed in the core layer of the particleboard. In general, as the a/W ratio decreased, the stiffness of the material increased, and the specimens with an a/W ratio of 0.1 showed brittle behavior. However, there was no statistically significant difference between a/W ratios of 0.5 and 0.7.